Suicide ideation and attempts among people with epilepsy in Addis Ababa, Ethiopia - Kelelemua Haile; Tadesse Awoke; Getinet Ayano; Minale Tareke; Andargie Abate; Mulugeta Nega (Annals of General Psychiatry, 2018)
Abstract Background Suicidal ideation and attempts are more frequent in people with epilepsy than in general population and suicide attempt increases the chance of later completed suicide. The aim of this study was to assess the prevalence and associated factors of suicidal ideation and attempt among people with epilepsy in Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia. Methods Institution-based cross-sectional study was conducted from May to June 2014 at Amanuel Mental Specialized Hospital among people with epilepsy. The pre-tested semi-structured questionnaire was used for interviewing the study participants. Logistic regression analysis was used to assess predictors of suicidal ideation and attempt. Results The study indicated that the prevalence of suicidal ideation and attempt among people with epilepsy were 29.8 and 14.1%, respectively. Poor social support, drug treatment for mental illness, had co-morbid depression, no seizure free within 1 year and family history committed suicide were significantly associated with suicidal ideation and attempt. Conclusion The prevalence of suicidal ideation and attempt in people with epilepsy found to be higher when compared to general population. Therefore, screening all epilepsy patients should be done for early diagnosis and treatment.